ANALISA TENTANG FAKTOR – FAKTOR YANG MEMPENGARUHI INFORMASI PADA SEKRETARIAT DAERAH KABUPATEN INDRAGIRI HULU - Ayuni, Saidati Wardata; ", Erman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The purpose of national development is to realize a just and prosperous society based on Pancasila and the Constitution - Constitution of the Republic of Indonesia Year 1945 Regional development is an integral part inseparable from national development. Regional development is directed to trigger equitable development and results - the results for the people's welfare. Government as development practitioners nowadays more dituntuk professionalism in providing and disseminating development information that is being implemented. For the dissemination of information in the conduct and policies of the government appointed bodies authorized to carry out the duties and functions of Public Relations (PR).Public Relations (PR) is a continuation of the process of determining policies, the provision of services to the community in a manner that is tailored to the interests of the person or golongan.Ada several factors that affect the role of Public Relations at the present time, including on the progress of information technology. Where information plays an important role in delivering policies and regional development. But in fact, the phenomenon that occurs is that the service system in the Regional Secretariat of Public Relations Indragiri Hulu is still inadequate in the areas of information in particular. This happens because of the low ability of the media information that is managed by the Public Relations Department in presenting the information up to date, fast, accurate, and interesting to follow. Then the lack of facilities and infrastructure are managed media information Public Relations Department of the Regional Secretariat Indragiri Hulu.Keywords: Information, Public Relation (PR)